α-Chymotrypsin-Induced Acetalization of Aldehydes and Ketones with Alcohols - Lan, Jin; Jiang, Guofang; Yang, Jiangnan; Zhu, Haibo; Le, Zhanggao; Xie, Zongbo (Synthesis, 2020)
This is the first report of a simple and general method for acetalization of aldehydes via an α-chymotrypsin-induced reaction under mild conditions. A broad range of aromatic and heteroaromatic aldehydes have been acetalized under neutral conditions in good yields using a catalytic amount of chymotrypsin.
Keywords: α-chymotrypsin; acetalization; biocatalysis; green chemistry